The Emergence of Alternative Sociotechnical Imaginaries in Argentina's Agricultural Sector: Lessons for Democracy and Sustainability - Melisa Deciancio; Karen M. Siegel (Politische Vierteljahresschrift, 2023)
The question of how various actors envision sustainability transitions and which visions are translated into policy agendas is an important aspect of the sustainability–democracy debate. Applying Jasanoff's concept of sociotechnical imaginaries, this paper examines how three alternative imaginaries of agricultural production—agroecology, organic production, and biodevelopment—have emerged in Argentina, as well as how they have established themselves economically and politically despite the dominance of the well-established soybean imaginary. Argentina's return to democracy in 1983 was crucial for the emergence of alternative imaginaries because it enabled a~new kind of relationship between the state and civil society that opened participation channels for alternative visions. Reflecting patterns that are also relevant to other South American countries, our analysis of the Argentinean case draws attention to the role inequality plays at different levels and its importance as an area for further research on the democracy–sustainability nexus.
Keywords: 320; Development; Bioeconomy; Transition; Soybean; Agroecology; Biodevelopment; Entwicklung; Bioökonomie; Transformation; Soja; Agrarökologie; Bioentwicklung